Inhibitory targeting cGAS-STING-TBK1 axis: Emerging strategies for autoimmune diseases therapy - Zhang, Min; Zou, Yan; Zhou, Xujun; Zhou, Jinming (Frontiers in Immunology, 2022)
The cGAS-STING signaling plays an integral role in the host immune response, and the abnormal activation of cGAS-STING is highly related to various autoimmune diseases. Therefore, targeting the cGAS‒STING‒TBK1 axis has become a promising strategy in therapy of autoimmune diseases. Herein, we summarized the key pathways mediated by the cGAS‒STING‒TBK1 axis and various cGAS‒STING‒TBK1 related autoimmune diseases, as well as the recent development of cGAS, STING, or TBK1 selective inhibitors and their potential application in therapy of cGAS‒STING‒TBK1 related autoimmune diseases. Overall, the review highlights that inhibiting cGAS‒STING‒TBK1 signaling is an attractive strategy for autoimmune disease therapy.